2015
DOI: 10.1366/14-07561
|View full text |Cite
|
Sign up to set email alerts
|

A Raman Spectroscopic Study of Cell Response to Clinical Doses of Ionizing Radiation

Abstract: The drive toward personalized radiation therapy (RT) has created significant interest in determining patient-specific tumor and normal tissue responses to radiation. Raman spectroscopy (RS) is a non-invasive and label-free technique that can detect radiation response through assessment of radiation-induced biochemical changes in tumor cells. In the current study, single-cell RS identified specific radiation-induced responses in four human epithelial tumor cell lines: lung (H460), breast (MCF-7, MDA-MB-231), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 41 publications
7
72
0
2
Order By: Relevance
“…We found that the difference in proteins was prominent, compared to other cellular components between the control and irradiated group at the cell level, suggesting that the radiation effect was concentrated in the majority of some amino acids molecules or deformation mode. 9 For amino acids in CNE2 cells ( Fig. 4(a)), the relative contents of protein bands such as tryptophan (the peaks at 875, 1552 and 1612 cm À1 ) and tyrosine (the peaks at 492 and 1612 cm À1 ) were signicantly different between the control and irradiated group (p < 0.05).…”
Section: Multivariate Analysis Of Raman Spectra From Npc Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…We found that the difference in proteins was prominent, compared to other cellular components between the control and irradiated group at the cell level, suggesting that the radiation effect was concentrated in the majority of some amino acids molecules or deformation mode. 9 For amino acids in CNE2 cells ( Fig. 4(a)), the relative contents of protein bands such as tryptophan (the peaks at 875, 1552 and 1612 cm À1 ) and tyrosine (the peaks at 492 and 1612 cm À1 ) were signicantly different between the control and irradiated group (p < 0.05).…”
Section: Multivariate Analysis Of Raman Spectra From Npc Cellsmentioning
confidence: 95%
“…6,7 The radioresistant lung and breast cells showed radiation-induced RS spectral features as glycogen accumulation at low RT doses, whereas the radiosensitive prostate cells showed some membrane phospholipid-related alterations. 8,9 Roman et al analyzed cytoplasmic and nuclear regions of irradiated prostate cancer cells (PC-3) and suggested various DNA damages located in those two regions. 10 Lasalvia et al observed that DNA was damaged in breast cells (MCF10A) irradiated by protons, in particular the O-P-O stretching mode at about 784 cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…RS has the potential to be more automated and adaptable to routine screening and provides a spectroscopic signature of all molecular constituents of the tissue sample, which facilitates the analysis and use of subtle molecular changes to classify different pathology and tissue states. Due to these pathology and tissue-specific spectroscopic signatures, RS has been used as a tool in histopathology [8][9][10][11][12][13][14] , and cytology [15][16][17][18] . It is based on inelastic light scattering and occurs when the biological sample is illuminated by monochromatic laser light.…”
Section: Introductionmentioning
confidence: 99%
“…RS has been used to detect changes in cells and tissues exposed to ionizing radiation. [15][16][17][18][19][20][21][22][23][24][25] Past studies on pure samples of concentrated DNA have shown radiation induced changes to DNA, 26,27 believed to be due to structural changes. Similar studies have shown detectable changes in proteins, and lipids.…”
Section: Raman Spectroscopy As a Label-free Technique For Biomedical mentioning
confidence: 99%
“…17,18 Similar studies in a lower, clinically relevant dose range from 2-10 Gy have also been performed. 21 One biomolecular change some of these studies detected was an increase of glycogen within radioresistant human lung cancer cells in vitro, 22 as well as in vivo using tumour xenographs of the same cells. 24 While these studies show great potential for using RS to detect biochemical changes in irradiated cells, they do not involve using RS for purposes of radiation dosimetry.…”
Section: Raman Spectroscopy As a Label-free Technique For Biomedical mentioning
confidence: 99%